What is holding back business process virtualization in the post-COVID-19 era? Based on process virtualization theory (PVT) - Feng, Yituo; Park, Jungryeol; Feng, Miao (Frontiers in Psychology, 2023)
The post-pandemic COVID-19 has been influential in accelerating the digital transformation of enterprises and business process virtualization. However, in a virtual working environment with no physical interaction, the psychological requirements of the communication between teleworkers and the negative impact of information systems are hindering the business process virtualization. Studying the relationship between the interaction between organizational members and job performance is an important part of organizational psychology. For an enterprise to maintain high-efficiency output, it is necessary to study psychological factors related to business process virtualization. This paper verified the factors hindering business process virtualization based on Process Virtualization Theory (PVT). The research was implemented on a sample of 343 teleworkers in China enterprises. The structure of the model of this study includes two aspects that hinder the business process virtualization: the psychological requirements of teleworkers (Sensory requirements, Synchronism requirements, Relationship requirements) and the negative effects of information systems (Information overload, Communication overload). The results show that teleworkers' sensory requirements, synchronism requirements, and communication overload negatively impact business process virtualization. However, unlike the results in the existing literature, the relationship requirements and information overload do not affect the business process virtualization. The results will help business managers, teleworkers, and information system developers develop strategies to address the negative factors hindering business process virtualization. In the so-called new “normal era,” our research will help companies to create a successful virtual work environment.